Improving Energy Efficiency in Brasov Romania - Mot, Manuela; Bose, Ranjan; Burduja, Sebastian; Ionescu-Heroiu, Marcel (World Bank, Washington, DC, 2016)
The Tool for Rapid Assessment of City Energy (TRACE) is used for conducting rapid assessments of energy use in cities. It helps prioritize sectors with significant energy savings potential, and identifies appropriate energy efficiency interventions across six sectors-transport, municipal buildings, water and waste water, public lighting, solid waste, and power and heat. It is a simple, low-cost, user-friendly, and practical tool that can be applied in any socioeconomic setting. While this work focuses on the growth poles in Romania, the analysis was limited to the boundary of the center city of Brasov, due to the difficulty of collecting individual indicators for all the constituent localities of a metropolitan area. The report details the analysis carried out and the recommendations derived as a result, for district heating maintenance and upgrade, non-motorized transport, public transport development, parking restraint measures, municipal buildings audit and retrofit, street lighting timing program, and active leakage of water and pressure management.